Whisper to the blood [compact disc, unabridged] - Stabenow, Dana (Stabenow, Dana. Kate Shugak series., 2009)
Between two suspicious murders and a series of attacks on snow mobilers up the Kanuyaq River, part-time P.I. and newly elected chairman of the Niniltna Native Association Kate Shugak has her hands full.